Population Pharmacokinetics of Vancomycin in Thai Patients - Tunggul Adi Purwonugroho; Suvatna Chulavatnatol; Yupaporn Preechagoon; Busba Chindavijak; Kumthorn Malathum; Pakwan Bunuparadah (The Scientific World Journal)
Population pharmacokinetics of vancomycin in Thai adult patients was determined by non-linear mixed-effects approach using 319 vancomycin serum concentrations from 212 patients. The data were best fitted by a two-compartment model and it was used to examine the effect of patient characteristics on the vancomycin pharmacokinetics. In the final model, there was a linear relationship between vancomycin clearance, CL (L/h), and creatinine clearance calculated by Cockcroft-Gault equation, CLCr (mL/min): CL=0.044×CLCr. Meanwhile, volume of central compartment, 𝑉1 (L), was linearly related with the age (years old): 𝑉1=0.542× Age. Intercompartment clearance (𝑄) and volume of peripheral compartment (𝑉2) was 6.95 L/h and 44.2 L, respectively. The interindividual variability for CL, 𝑉1, 𝑄, and 𝑉2 was 35.78, 20.93, 39.50, and 57.27%, respectively. Whereas, the intraindividual variability was 4.51 mg/L. Final model then was applied to predict serum vancomycin concentrations on validation group. Predictive performance revealed a bias of −1.43 mg/L (95% CI: −5.82–2.99) and a precision of 12.2 mg/L (95% CI: −1.60–26.16). In conclusion, population pharmacokinetic of vancomycin in Thai adult patients was developed. The model could be used to create vancomycin dosage regimen in the type of patient similar with the present study.